Analysis of the Effect of Product Quality, Brand Image and Customer Relations on Customer Loyalty CV. Globalindo Sejati - Evi Novalin Bako; Asmiati Nabila (Jurnal Mantik, 2020)
This study aims to determine the analysis of the effect of product quality on consumer loyalty, analysis of the influence of brand image on consumer loyalty, analysis of the influence of customer relations on customer loyalty and analysis of the influence of product quality, brand image and customer relations on consumer loyalty. This is quantitative research. The population in the study is customers of CV. GlobalindoSejati Medan, amounting to 100 person and the determination of sample size using the Slovin formula so that the sample in this study was 50 people while the sampling technique used incidental sampling. Sources of data come from primary data, namely observation, interviews, questionnaires that have been tested for validity and reliability and from secondary data. Data analysis method used is multiple linear regression analysis, partial test (t-test), simultaneous test (F test), and determination coefficient (R2). Based on the results of multiple linear analysis obtained Y = 20,107 + 0,429X1 + 0,322X2 + 0,321X3 + e which shows that product quality , brand image, and customer relations (Customer relations) have a positive relationship to consumer loyalty CV. GlobalindoSejati. While the test results (t) or partial shows that partially the quality of the product, brand image and customer relations have a positive and significant effect on consumer loyalty at CV. Global GlobalSejati where the value of t arithmetic for the product quality variable is t count = 7,552> t table 2.012, brand image variables also have a positive and significant effect on consumer loyalty which can be seen t count = 2.915> t table 2. 012 and customer relations variables also have a positive and significant effect on consumer loyalty which can be seen t count = 3.218> t table 2,012. The results of the coefficient of determination (R2) with an adjusted R2 value of 0.675 (67.5%). So that it can be said that 67.5% variation of the dependent variable namely product quality, brand image, and customer relationship on the model can explain consumer loyalty CV. GlobalindoSejati.